Hukum Denda dalam Keuangan Publik Islam di Indonesia - Aziz, Fathul Aminudin (Fakultas Syariah IAIN Purwokerto, 2018)
Fines are sanctions or punishments that are applied in the form of the obligation to pay a sum of money imposed on the denial of a number of agreements previously agreed upon. There is debate over the status of fines in Islamic law. Some argue that fines may not be used, and some argue that they may be used. In the context of fines for delays in payment of taxes, in fiqh law it can be analogous to ta'zir bi al-tamlÄ«k (punishment for ownership). This can be justified if the tax obligations have met the requirements. Whereas according to Islamic teachings, fines can be categorized as acts in order to obey government orders as taught in the hadith, and in order to contribute to the realization of mutual benefit in the life of the state. As for the amount of the fine, the government cannot arbitrarily determine fines that are too large to burden the people. Penalties are applied as a message of reprimand and as a means to cover the lack of the state budget.